Diagrams, Timelines, and Tables—Oh, My! Fostering Graphical Literacy. (22nd May 2013) - Roberts, Kathryn L.; Norman, Rebecca R.; Duke, Nell K.; Morsink, Paul; Martin, Nicole M.; Knight, Jennifer A.
Abstract: The Common Core State Standards place unprecedented emphasis on visual text—appropriately so, as visual components are increasingly ubiquitous in many kinds of text. This shift in emphasis requires substantial changes in our teaching. Concepts of print need to be expanded to include concepts of graphics, and specific graphical devices, such as diagrams, timelines, and tables, need to become the focus of systematic instruction. This article shares research‐based instructional practices that may support children's development in this increasingly important area.